Interaksi Kompetensi Kepribadian Guru dengan Kepuasan Kerja - Sukoyo Sukoyo; Juhji Juhji (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
This article aims to analyze and discribe the interaction of the teacher's personality competence with job satisfaction. This article uses the correlational method. A total of 68 madrasa teachers in South Tangerang were used as respondents. Primary data was obtained through the Google Forms platform, which was distributed within two weeks. At the same time, secondary data was obtained from references related to job satisfaction and personality competence. The instrument used in the study was a questionnaire compiled according to a validated Likert scale. Data analysis using a simple regression test. The results showed that there was an interaction between the teacher's personality competence and job satisfaction. The study of both is discussed further. The recommendation of this study is that teachers can improve personality competencies because it is proven to be related to their job satisfaction in madrasas.